Bacterial Transformation and Processing of Diatom-Derived Organic Matter: A Case Study for Skeletonema dohrnii - Liu, Yang; Wang, Xueru; Sun, Jun (Frontiers in Microbiology, 2022)
Bacterial transformation and processing of phytoplankton-derived organic matter are extremely important for the formation of ubiquitous organic matter (OM) in aquatic ecosystems. Heterotrophic bacteria convert OM into biomass and recycle inorganic components, contributing to the production of microbial food webs. While phytoplankton-derived organic matter is commonly studied, the transformation and processing of dissolved OM (DOM) and lysate OM (LOM) by culturable epiphytic bacteria remains poorly understood. In this study, cultivable epiphytic bacteria from the marine diatom, Skeletonema dohrnii, were isolated, purified, and identified. Three bacteria, Roseobacteria sp., Marinobacter sp., and Bacillus sp., were selected to study the transformation and processing of S. dohrnii-derived DOM and LOM using excitation-emission matrix (EEM) fluorescence methods, and bacterial abundance, dissolved organic carbon (DOC) concentration, and transparent exopolymer particle (TEP) content were measured. Meanwhile, the bacterial transformation of DOM and LOM was further evaluated by the fluorescence index, biological index, β/α, and humification index. The primary fluorophores, peak A (humic-like), peak C (humic-like), peak M (humic-like), peak B (protein-like), and peak T (tryptophan-like), were present in the sample. The fluorescence of DOM and LOM was dominated by protein-like signal that became increasingly humic-like over time, suggesting that more complex molecules (e.g. recalcitrant OM) are being produced. The fluorescence of DOM and LOM was dominated by a protein-like signal that became increasingly humic-like over time, suggesting that epiphytic bacteria produced more complex molecules. Results showed that the bacteria utilized LOM more rapidly than DOM. While the three bacteria transformed OM to different degrees, all were able to facilitate microbial reprocessing of OM into refractory OM.